Catskills Pet Rescue : Claws for Suspicion - Book 3 - Blake, Deborah (Writer of paranormal) (New York : Berkley Prime Crime, 2022)
Kari Stuart is finally starting to relax into her role as the new owner of the Serenity Sanctuary and is looking forward to the various fun autumn activities in the beautiful Catskills town of Lakeview, like the annual Oktoberfest celebration. Its time for friends and quality bonding with handsome vet Angus McCoy. Until the unexpected arrival of her unpleasant ex-husband, Charlie Smith. He comes bearing a shocking revelation--the paperwork on their divorce never went through, and they are still married. Worse yet, he thinks this entitles him to half of her lottery winnings--although hell happily take partial ownership of the sanctuary instead. Kari isnt sure if hes telling the truth, or if its just another one of Charlies lies. But things go from bad to worse when an unexpected death makes Kari the main suspect in a murder investigation. Will she and Queenie be able to find the real killer and keep the home theyve built at the sanctuary safe, or is their string of luck finally tapped out?
Keywords: Animal rescue -- Fiction; Cats -- Fiction; Oktoberfest -- Fiction; Lottery winners -- Fiction; Murder -- Investigation; Fiction; Human-animal relationships -- Fiction; Catskill Mountains (N.Y.) -- Fiction; Cozy mystery fiction; Cozy mysteries